Cellular uptake of cyclotide MCoTI-I follows multiple endocytic pathways - Contreras, Janette (2011)
Cyclotides are plant-derived proteins that naturally exhibit various biological activities and whose unique cyclic structure makes them remarkably stable and resistant to denaturation or degradation. These attributes, among others, make them ideally suited for use as drug development tools. This study investigated the cellular uptake of cyclotide, MCoTI-I in live HeLa cells. Using real time confocal fluorescence microscopy imaging, we show that MCoTI-I is readily internalized in live HeLa cells and that its endocytosis is temperature-dependent. Endocytosis of MCoTI-I in HeLa cells is achieved primarily through fluid-phase endocytosis, as evidenced by its significant colocalization with 10K-dextran, but also through other pathways as well, as evidenced by its colocalization with markers for cholesterol-dependent and clathrin-mediated endocytosis, cholera toxin B and EGF respectively. Uptake does not appear to occur only via macropinocytosis as inhibition of this pathway by Latrunculin B-induced disassembly of actin filaments did not affect MCoTI-I uptake and treatment with EIPA which also seemed to inhibit other pathways collectively inhibited approximately 80% of cellular uptake. As well, a significant amount of MCoTI-I accumulates in late endosomal and lysosomal compartments and MCoTI-I-containing vesicles continue to exhibit directed movements. These findings demonstrate internalization of MCoTI-I through multiple endocytic pathways that are dominant in the cell type investigated, suggesting that this cyclotide has ready access to general endosomal/lysosomal pathways but could readily be re-targeted to specific receptors through addition of targeting ligands.